Independence of The Modern Darussalam Gontor Education System (PMDG) In Establishing The Personality of Perspective Interest and Tarbawi Hadith - Ramdhani, Ashary (Devotion : Journal of Research and Community Service, 2023)
Worldwide educational institutions whose systemsare independent, do not follow the example of experts butall systems move and work independently, without involving or there is dependence and attachment to outside parties. Until now, the Islamic educational institution Pondok Modern Darussalam Gontor (PMDG) is in the independence of the system, on the one hand experts are always looking for the best educational institution system so that it continues to develop not lagging behind the times, and on the other hand many local islamic boarding schools have fallen because they were crushed by the times, Pondok Modern Darussalam Gontor still exists in the same system without changes,  forming the personality of students who are ready to appear as national and even international figures. Against the backdrop of this situation, it was studied how the interpretation and hadith views of tarbawi on the independence of the Darussalam Gontor Modern Lodge system. The independence of the system born of experience is not the theory and reference of educational experts. The method used to discuss this study is with literature studies and interviews. The independence system created by Pondok Modern Darussalam Gontor is: 1) Leadership; 2) Parenting; 3) Teaching; 4) Regeneration; and 5) Funding, which is transformed to students, teachers, families, guardians of students, the community, community leaders and the government. This plays a very important role  in shaping personality in the form of work character and work competence for the glory of Indonesian national civilization. It was concluded that the independence of the Pondok Modern Darussalam Gontor system according to the interpretation and hadith of tarbawi is muhasabah as TQC (Total Quality Control) which becomes the basic system of independence, the foundation of the entire system and  forms the quality of the existing systems. This TQC is easily adopted by other Islamic Educational Institutions